2018
DOI: 10.1002/jor.24141
|View full text |Cite
|
Sign up to set email alerts
|

High muscle co‐contraction does not result in high joint forces during gait in anterior cruciate ligament deficient knees

Abstract: The mechanism of knee osteoarthritis development after anterior cruciate ligament injuries is poorly understood. The objective of this study was to evaluate knee gait variables, muscle co-contraction indices and knee joint loading in young subjects with anterior cruciate ligament deficiency (ACLD, n = 36), versus control subjects (n = 12). A validated, electromyography-informed model was used to estimate joint loading. For the involved limb of ACLD subjects versus control, muscle co-contraction indices were hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 44 publications
4
24
2
Order By: Relevance
“…T 2 relaxation time values are typically higher in the patellar and trochlear cartilage than the weight‐bearing tibiofemoral cartilage . Walking speeds also vary both within and across studies, and our mean walking speed (1.61 m/s) is very similar to previous studies in separate cohorts from our lab (means of 1.5–1.6 m/s), albeit similar to or faster than other cohorts . Our study sample was young and free of any serious previous or concomitant injury.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…T 2 relaxation time values are typically higher in the patellar and trochlear cartilage than the weight‐bearing tibiofemoral cartilage . Walking speeds also vary both within and across studies, and our mean walking speed (1.61 m/s) is very similar to previous studies in separate cohorts from our lab (means of 1.5–1.6 m/s), albeit similar to or faster than other cohorts . Our study sample was young and free of any serious previous or concomitant injury.…”
Section: Discussionsupporting
confidence: 76%
“…The present study has cartilage T 2 relaxation times and walking speeds that fall within the range found in the literature . Cartilage T 2 relaxation time values, however, vary greatly in the literature, from approximately 23 ms in the deep layers of the medial femoral cartilage of ACL‐injured knees at baseline to higher than 60 ms in the superficial central trochlear cartilage 3 years after ACLR .…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Tsai et al reported that greater co‐activation was associated with greater tibiofemoral compressive force during single‐leg landing in individuals with ACLR. However, Khandha et al found that though co‐activation was greater in the affected limb in ACL‐deficient individuals during gait, co‐activation was not associated with tibiofemoral compressive force, and the compressive force was lower in the ACL‐deficient limb. Wellsandt et al reported that the compressive force was consistently lower in their PTOA cohort 6 months, 1 year, and 2 years post‐ACLR (effect sizes = 1.39, 0.92, and 0.42, respectively) compared with those who did not develop PTOA, and that co‐activation was negatively correlated with compressive force.…”
Section: Discussionmentioning
confidence: 98%
“…Meyer et al (2013) used an implant also consisting of 6 DoFs (3 for the force and 3 for the moment components) but the geometry varied slightly compared to the instrumented prosthesis used in the other 2 studies. The studies, which used an EMG-informed MSK model (Kumar et al, 2013;Winby et al, 2013;Manal et al, 2015;Saxby et al, 2016;Wellsandt et al, 2017;Khandha et al, 2019), based their calculations of the internal KCF on the same equations (Lloyd and Besier, 2003;Winby et al, 2009), which allow separate calculation of the medial and lateral compartmental loading. An extension (Lloyd and Buchanan, 1996) of the generic 1 DoF knee model (Delp et al, 1990) was used as the anatomical model.…”
Section: Estimation Of External Joint Moments and Internal Joint Contmentioning
confidence: 99%